INFLUENCE OF PARTICLE SIZE AND PARTICLE DEPOSITION OF INHALED MEDICATION IN LUNG DISEASE: A COMREHENSIVE REVIEW (International Journal of Pharmaceutical Sciences and Drug Research, 2022)
Drug particles less than 5 μm have the greatest probability of deposition in the lung, whereas those less than 2 μm tend to be concentrated in the alveoli. A large proportion of particles within the 2-5 μm range are present in the dose released from the inhaled drug, providing a relatively even distribution across the lungs. The efficient need for inhaled therapy highly depends on the essence of the method of drug delivery and the patient's ability to correctly use the system. A large range of inhaler products, each with positive and negative aspects, are on the market. It facilitates the administration of a lower dose; there is a quicker onset of action and less severe side effects. The deposition of the inhaled drug in the lung is dependent on particle size, inhalation technique and the type of inhaler device. Importance of particle size distribution and Particle aerodynamic diameter, Influence of environmental humidity on particle size Particle deposition in the airways, Methods to identify drug deposition in lungs, Physiological factors which affect the therapeutic efficacy of pulmonary delivery drugs. The nano and micro size particles is a mainstay of treatment for a variety of pulmonary diseases because they provide a platform to deliver drugs directly reliably and inexpensively to the disease site, thus allowing for a minimum amount of drug to be used and minimize side effects.